2004
DOI: 10.1023/b:pham.0000012160.00222.55
|View full text |Cite
|
Sign up to set email alerts
|

Local and Systemic Immune Responses to Intratracheal Instillation of Antigen and DNA Vaccines in Mice

Abstract: Purpose. The purpose of this study was to determine the immunization efficacy of antigen and DNA vaccines after delivery to the lung, to assess the integrity of the pulmonary tissue after vaccination, and to elucidate mechanisms involved in the induction of immunity. Methods. Ovalbumin, the plasmid encoding ovalbumin, the hepatitis B surface antigen (HBsAg), or plasmid encoding HBsAg were intratracheally instilled or injected in quadriceps in mice. The immune response and its Th polarization were analyzed over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Although published studies, including ours (13), suggest that the mucosal route of administration, including nasal, pulmonary and vaginal routes, are a viable non-invasive alternative for delivering HBsAg antigen (44)(45)(46)(47), no studies have specifically investigated the role of particle size in generation of immune response upon inhalational delivery. This manuscript is the first to investigate the effect of particle size on the uptake by rat alveolar macrophages and relate the sizedependent uptake to in-vivo immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Although published studies, including ours (13), suggest that the mucosal route of administration, including nasal, pulmonary and vaginal routes, are a viable non-invasive alternative for delivering HBsAg antigen (44)(45)(46)(47), no studies have specifically investigated the role of particle size in generation of immune response upon inhalational delivery. This manuscript is the first to investigate the effect of particle size on the uptake by rat alveolar macrophages and relate the sizedependent uptake to in-vivo immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The only other methodology reported for direct delivery of dry powders is tracheostomy (Lombry et al, 2004;Wong, 2007;Fernandes and Vanbever, 2009). This method involves a surgical incision to expose the trachea and the placement of powders into a cannula that is inserted towards the lung or directly into the upper respiratory tract.…”
Section: Preclinical Inhalation Methodologiesmentioning
confidence: 99%
“…Even though many investigators reported the possible side-effects of inducing local inflammation by CpG ODN, recent evidence has shown that DNA vaccines with CpG ODN as an adjuvant delivered to the lung does not induce any local signs of inflammation [63]. This finding implies that the increased number and unmethylated status of CpG motifs, particularly when present in a particular base context, may be identified as a 'foreign' molecular pattern and thus activate appropriate immune responses.…”
Section: Possible Side-effects Of Cpg Odnsmentioning
confidence: 99%
“…This finding implies that the increased number and unmethylated status of CpG motifs, particularly when present in a particular base context, may be identified as a 'foreign' molecular pattern and thus activate appropriate immune responses. Fortunately, no direct evidence that bacterially-derived DNA causes clinically significant damage has yet been reported [63].…”
Section: Possible Side-effects Of Cpg Odnsmentioning
confidence: 99%